1990
DOI: 10.1080/00268979000101801
|View full text |Cite
|
Sign up to set email alerts
|

The pressure second virial coefficient of vibrating symmetric triatomic molecules

Abstract: The effect of molecular flexibility on the pressure second virial coefficient B has been evaluated for both linear molecules related to CS 2 and nonlinear symmetric triatomic molecules derived from CS~. Our results show that these effects will not be significant in evaluating pairwise intermolecular potentials for these molecules. Earlier, we found this also to be the case for linear diatomic molecules. This result is different from the case of water, where much larger contributions (up to 10%) were reported b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In view of these facts, Zhu et al 65 reported a new potential model for liquid CS2 composed of intermolecular LJ atom-atom and Coulombic electrostatic terms plus a third term describing the intramolecular harmonic vibrations. This model has been further used in a number of forthcoming simulation studies mainly at ambient conditions 31,[75][76][77] .…”
Section: A Potential Modelmentioning
confidence: 99%
“…In view of these facts, Zhu et al 65 reported a new potential model for liquid CS2 composed of intermolecular LJ atom-atom and Coulombic electrostatic terms plus a third term describing the intramolecular harmonic vibrations. This model has been further used in a number of forthcoming simulation studies mainly at ambient conditions 31,[75][76][77] .…”
Section: A Potential Modelmentioning
confidence: 99%
“…Finally, we will also investigate the effect of electrostatic forces (dipole and quadrupole moments, etc.) and molecular flexibility (such as bond angle vibrations [27]) on these transport properties. Some work has been done previously on the effect of electrostatic forces on pure fluids [12], but our main interest will be to study mixtures.…”
Section: I Approximationmentioning
confidence: 99%